ANALISIS UNSUR CITRAAN PUISI â€œDI NEGERI AMPLOPâ€ KARYA KH. A. MUSTOFA BISRI - Anwar Nada; Hairunisa Hairunisa (Universitas Khairun, 2021)
This research was conducted with the aim of explaining the elements of the poetry imageryâ€Di Negeri Amplopâ€ karya KH. A. Mustofa Bisri. The method used in this research is descriptive qualitative method. The data used are primary data and secondary data, data sources related to where the data obtained by the subject of this study are poetry texts. The data collection techniques used were observation and dokumentation. The data analysis tecnique used was data reduction, and conclusion. Based on the results of data analysis, it can be concluded that there are 7 images, namely; (1) visual images is an image generated by the sense of sight (eye), (2) auditory image is an image produced by mentioning or deciphering sound, (3) touch image is an image that chan be self by the sense of touch (skin), (4) olfactory imagery is an imagery related to the impression or image produced by the sense of smell, (5) tasting image is an image related to the impression or image produced by the sense of taste, and (6) feeling image is an expression of the poets by KH. A. Mustofa Bisri, there were 4 images obtained during the 5 days of the study, namely, (1) visual images, images created by the sense of sight (eyes), are explained about the conditions in this country which are made as materialistic countries or people who are concerned with power, property, money, etc. (2) hearing images produced by mentioning or describes the sound of a voice, which explains how cruel the ruler is who silences the mouths of people who want to convey the truth (3) motion images of something that seems to be moving, which explains the envelopeÂ referred to here is not containng a letter containing envelopes containing money, envelopes can move anywhere and for anyone (4) imagery of feelings, expression of feelings of the poet to express these feelings, explain the poet to express his frustation by using a subtle satire tone to a ruler who is greedy for power, what is right can be wong and wrong can be right with an envelope.